Analysis of air pollution distribution in West Pasaman Regency effects of palm oil mills - Yosenov, Herri; Bachtiar, Vera Surtia; Zulkarnaini, Zulkarnaini (Universitas Negeri Padang, 2023)
The purpose of this research was to identify sources of pollution and analyze the level of pollution for the parameters of TSP (Dust), particulates, NO2, and SO2 and to map their distribution. The research was conducted at 9 (nine) palm oil mills spread throughout West Pasaman Regency. The data used are primary and secondary data. The primary data includes particulates, TSP, SO2, and NO2 gases. Secondary data consists of test results data at the Environmental Service in 2017, morphological data, and factory location maps. Data processing methods include statistical analysis of Shapiro Wilk. Then proceed with descriptive analysis to determine the characteristics of the range of minimum and maximum values of air pollution distribution. Spatial analysis of the overlay type was carried out using a GIS application. Particulate, TSP, NO2 and SO2 test results at each location have met the required air quality standards. mapping the distribution of air pollutants for the parameters TSP (Dust), NO2 and SO2 with the direction of their spread according to the wind direction. Comparison with the latest regulations, namely PP Number 22 of 2021 Appendix VII, shows that the test results are still below the set quality standards. With the test values obtained and the meteorological factors in each company, it shows that there is no significant effect of pollutant content from sources of pollution on the environment around the palm oil mills.